Organic ligands in whale excrement support iron availability and reduce copper toxicity to the surface ocean - Patrick J. Monreal; Matthew S. Savoca; Lydia Babcock-Adams; Laura E. Moore; Angel Ruacho; Dylan Hull; Logan J. Pallin; Ross C. Nichols; John Calambokidis; Joseph A. Resing; Ari S. Friedlaender; Jeremy Goldbogen; et al. (Communications Earth & Environment)
Abstract Nutrient recycling by marine megafauna is a key ecosystem service that has been disturbed by anthropogenic activity. While some hypotheses attribute Southern Ocean ecosystem restructuring to disruptions in micronutrient cycling after the elimination of two million great whales, there is little knowledge of trace metal lability in whale excrement. Here we measured high concentrations of dissolved iron and copper in five baleen whale fecal samples and characterized micromolar levels of organic metal-binding ligands as a proxy for their availability. The iron-ligand pool consisted of weakly-binding ligands and intermediate-binding ligands which enhanced iron stability and potential bioavailability. In comparison, 47 novel strongly-binding metallophores dominated copper-binding, curtailing its potential toxicity. These results illustrate how marine megafauna transform prey biomass into highly-labile micronutrients that they inject directly into the surface ocean, a mechanism whaling reduced by over 90%. Thus, the rapid restructuring of pelagic ecosystems through overharvesting may cause large biogeochemical feedbacks, altering primary productivity and carbon sequestration processes in the ocean.